Bhāratera ādhunika śilpakalāra nārībiśva - Ghoṣa, Mr̥ṇāla (Bhirāsata Ārṭa Pābalikeśana, 2023)
Depiction of women in modern Indian art.
Literaturverzeichnis: Seite 401-413
Keywords: Women in art.; Art; Indic.